2018
DOI: 10.1080/14786419.2018.1455049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis leaf, bud, capsule and seed crude extracts

Abstract: Well diffusion method was used to evaluate the antibacterial activity of Eucalyptus camaldulensis, while the antifungal effect was assessed by calculating the reduction percent in the radial growth of mycelia. The inhibition zones exerted by E. camaldulensis crude extracts varied significantly (p ≤ 0.01). The capsule crude extract (acetone 30%) highly inhibited the growth of Acinetobacter baumannii (35 mm clear zone). The highest antifungal activity was against Rhizopus stolonifer with a reduction percent in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
(4 reference statements)
0
7
1
Order By: Relevance
“…A study on the comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis revealed that both the type and concentration of the solvent greatly affected the antimicrobial properties of the plant [58]. It was reported that the 30% acetone extract of Eucalyptus camaldulensis showed the highest inhibition of Acinetobacter baumanni [58]. This trend was also observed when the acetone extracts of Acanthus polystachyus and Keetia gueinzii were tested against the gram-positive Bacillus cereus pathogen.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study on the comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis revealed that both the type and concentration of the solvent greatly affected the antimicrobial properties of the plant [58]. It was reported that the 30% acetone extract of Eucalyptus camaldulensis showed the highest inhibition of Acinetobacter baumanni [58]. This trend was also observed when the acetone extracts of Acanthus polystachyus and Keetia gueinzii were tested against the gram-positive Bacillus cereus pathogen.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, acetone extracts had the highest total phenolic, total flavonoid, and tannin content. A study on the comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis revealed that both the type and concentration of the solvent greatly affected the antimicrobial properties of the plant [58]. It was reported that the 30% acetone extract of Eucalyptus camaldulensis showed the highest inhibition of Acinetobacter baumanni [58].…”
Section: Discussionmentioning
confidence: 99%
“…The pronounced antioxidant and antibacterial action of eucalyptus leaf extracts has been experimentally confirmed. Eucalyptus leaves contain substances such as cineole and eucalypton, which are able to inhibit free radical processes [10][11][12]. However, there are no data on the use of eucalyptus leaf extracts as antioxidants for oils and oil-containing products, the effect of these antioxidants on the indicators of peroxide and acid numbers, which reflect the degree of product spoilage and the presence of harmful substances.…”
Section: Planning Of Experimental Research and Processing Of Resultsmentioning
confidence: 99%
“…After 4 days, the diameter of the pathogen colony (cm) was recorded. The inhibition percentage (I) was calculated using the following formula ( Nasr et al, 2019 ):…”
Section: Methodsmentioning
confidence: 99%